FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN MEDIASI KINERJA PERUSAHAAN - Andreas, Jonathan; Hadi, Hadi (Jurnal Paradigma Akuntansi, 2024)
The Purpose of this study is to determine the impact of Board Independence, Foreign Ownership, and Capital Structure on Firm Value with the Mediation of Firm Performance. This Research uses data from manufacturers company listed on the Indonesia Stock Exchange from 2018 to 2020. The sample was selected using Purposive Sampling and the results are 21 Companies. The data was processed by SmartPLS 3.3.9 application. The results of this research showed that Board Independence has a negative and significant impact on firm value, Foreign Ownership has a positive and significant impact on firm value, Capital Structure has a positive but not significant impact on firm value,Board Independence and Foreign Ownership has a positive and significant impact on Firm Performance, Capital Structure has a negative and significant impact on Firm Performance, Board Independence has a positive and significant impact on firm value with firm performance mediation, Foreign ownership has a positive and significant impact on firm value with firm performance mediation, capital structure has a negative and significant impact on firm value with firm performance mediation, and firm performance has a positive and significant impact on firm value.